東南極Lützow-Holm岩体に産する高カリウム貫入岩におけるマグマ混合の痕跡 - 宮本, 知治; 山下, 勝行; 島田, 和彦; 岡野, 修; 角替, 敏昭; D.J.Dunkley; 加藤, 睦実; Miyamoto, Tomoharu; Yamashita, Katsuyuki; Shimada, Kazuhiko; Okano, Osamu; Tsunogae, Toshiaki; et al. (2014)
conference object